From Wachirayanwisat to Phu Sao Kha Loa: Copyright Culture in the History of Thai Creative Works - Saengthong, Pichet (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 1 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This article analysed the social and cultural phenomena related to the usage of copyright law in Thai society. The research questions of this article are: how does mindset about copyright in Thai society relate to culture, class, and tradition? and how does this relationship support or cause problems of copyright law enforcement at present? The article only analysed documents. The results revealed that in Thailand, mindset about copyright in history did not emphasize the principle of morality and economy. The copyright particularly focused on social aspect that creative work was the assets of community and society inevitably because of the lack of seeking economic values from creative work. Besides, nowadays, the problems of copyright Infringement in Thai creative works originally came from culture. As a result, creators did not receive appropriate financial return from creative works.